Advances in biosensor technology for illicit drug detection enable effective wastewater surveillance - Xu, Qihang; Guo, Ying; Niu, Gang; Wu, Heping; Coulon, Frederic; Yang, Zhugen (American Chemical Society (ACS), 2026)
Drug abuse has been a global public health challenge, requiring robust and timely strategies for monitoring drug consumption at the community level. Wastewater-based epidemiology (WBE) offers population-scale insights by analyzing drug biomarkers in sewage, yet conventional analytical methods can be time-consuming and resource-intensive. Biosensor technology is rapidly emerging as a promising tool for detecting illicit drugs in complex wastewater matrices, offering significant advantages in speed, specificity, and cost-effectiveness over conventional analytical methods. This review explores the emerging role of biosensor technology in enhancing WBE for illicit drug detection. We first outline the principles of WBE and discuss conventional analytical techniques used in wastewater drug surveillance, noting their limitations in cost, throughput, and real-time applicability. Next, we examine key biosensor platforms encompassing electrochemical, optical, and other transducer-based designs and highlight their capacity to rapidly and selectively detect target drugs or metabolites in complex wastewater matrics. We then address the principal challenges of biosensor deployment in WBE, including sample matrix interference, sensor fouling, and the need for calibration and standardization. Finally, we identify critical research gaps, such as further miniaturization, multiplexed detection, and integration with Internet of Things (IoT) and big data analytics. By merging biosensor innovation with WBE, this multidisciplinary approach promises more efficient, adaptable, and community-focused solutions for tracking illicit drug trends and informing public health policy.
Keywords: illicitdrug; biosensor; public health; wastewater-basedepidemiology; real-time monitoring; point-of-need; 3401 Analytical Chemistry; 34 Chemical Sciences; 40 Engineering; 46 Information and Computing Sciences; 4605 Data Management and Data Science; Substance Misuse; Bioengineering; Drug Abuse (NIDA only); 4.1 Discovery and preclinical testing of markers and technologies; 3 Good Health and Well Being